“UNDERSTANDING LITERARY DEVICES AND THEIR IMPACT ON WRITING STYLES: TEACHING STUDENTS TO ANALYZE TEXTS CRITICALLY” - Sevara Abdusharof qizi Mambetova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: The aim of this article is to explore the significance of literary devices in shaping meaning, tone, and style in literature. It seeks to enhance students' critical analysis skills through effective teaching strategies, fostering deeper engagement with texts and improving their ability to articulate interpretations and appreciate nuanced literary elements.